Dietary phosphorus and feeding regimens modulate egg production, quality, and serum parameters in laying hens aged 61-80 weeks (Asian Journal of Medical and Biological Research, 2025)
Effective management of nutrients and feeding practices is essential to sustain egg production, maintain egg quality, and support the health of aging laying hens while optimizing resource use. This study examined the influence of dietary available phosphorus (AP) and quantitative feeding levels (QFL) on egg production, egg quality, and serum biochemical traits in Lohman Brown laying hens. A total of 540 hens, 60 weeks old, were assigned in a 2×3 factorial design, combining two AP levels (0.32% and 0.45%) with three feeding levels (90%, 95%, and 100% of standard intake). Each treatment included five replicates of 18 hens, and the experiment lasted 20 weeks following a 7-day acclimation period. Results showed that production performance was significantly affected by feeding level (P < 0.01), whereas AP levels had no significant impact. Egg production declined as feed restriction increased (P < 0.01), though no significant difference occurred between the 95% and 100% feeding groups. Egg weight, daily egg mass, and feed conversion ratio also decreased linearly with higher restriction (P < 0.01). Most egg quality traits were unaffected, except yolk color, which was greater at 0.45% AP (P < 0.01). Serum albumin decreased in the 90% feeding group (P < 0.05) but remained similar between 95% and 100% feeding levels. No significant interactions were detected between AP and QFL for serum biochemical indices. Overall, feeding hens at 95% of the recommended intake with 0.32% AP effectively maintained egg production, quality, and health, indicating that moderate feed restriction combined with adequate phosphorus can reduce feed costs without compromising performance in late-phase laying hens.Asian J. Med. Biol. Res. 2025, 11(4), 88-96